The Effectiveness of the Student Team Achievement Division (STAD) Cooperative Learning Model in Enhancing Pre-Service Teachersâ€™ Scientific Attitudes in Learning Vertebrate Zoology - Kodri Madang; Eng Tek Ong (Jurnal Penelitian Pendidikan IPA, 2023)
The STAD Cooperative Learning Model not only helps students understand Vertebrate Zoological concepts but also prepares prospective teachers with a good scientific attitude to teach. This study aims to analyze the use of the STAD which has a positive impact on the scientific attitudes of pre-service teachers. This study uses a quasi-experimental method withÂ a static-group comparison design. A sample of 85 pre-service teachers of Biology Education at Sriwijaya University were divided into a treatment group (STAD) and a control group (traditional methods) for a nine-week period. The Likert scale questionnaire was used, meeting sufficient validity and reliability standards to measured 12 subdimensions of scientific attitudes. The data was analyzed using MANOVA. The findings showed that the STAD significantly affected seven subdimensions: curiosity, flexibility, critical-mindedness, awareness of the non-absolute truth, belief in the orderliness of nature, carefulness, and optimism. However, there are five not significant subdimensions: honesty, lack of prejudice, tolerance, perseverance, and motivation. These findings suggest the STAD method can be effective in promoting positive scientific attitudes among pre-service teachers. The study's implications for teaching practices in promoting positive scientific attitudes are significant, and further research in this area is warranted.